Analisis Manajemen Keuangan UMKM Kuliner di Pantai Tanjung Bias (Financial Management Analysis of Culinary MSMEs on Tanjung Bias Beach) - Ningsih, Nurul Hidayati Indra; Wirastomo, Handoyo; Asidah, Erwin; Budiman, Saiful Bahri; Andika, Hiffal Sandi; Amin, Fajar Sadikul (STIE Malangkucecwara, 2025)
This study aims to analyze the financial management practices among MSMEs in Pantai Tanjung Bias, Desa Senteluk, Kecamatan Batulayar. A qualitative research method was employed to gain in-depth insights into the financial management challenges and practices within these enterprises. Data were collected through in-depth interviews, participant observation, and documentation, involving five MSMEs. The results indicate that financial management practices among the MSMEs are generally manual and lack technological integration, with varying degrees of complexity. The study also highlights the need for enhanced financial training and the adoption of digital tools to improve efficiency and accuracy in financial reporting.